If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 + 2x = 8x + -3 + -1x Reorder the terms: -3 + 4x + 2x = 8x + -3 + -1x Combine like terms: 4x + 2x = 6x -3 + 6x = 8x + -3 + -1x Reorder the terms: -3 + 6x = -3 + 8x + -1x Combine like terms: 8x + -1x = 7x -3 + 6x = -3 + 7x Add '3' to each side of the equation. -3 + 3 + 6x = -3 + 3 + 7x Combine like terms: -3 + 3 = 0 0 + 6x = -3 + 3 + 7x 6x = -3 + 3 + 7x Combine like terms: -3 + 3 = 0 6x = 0 + 7x 6x = 7x Solving 6x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 6x + -7x = 7x + -7x Combine like terms: 6x + -7x = -1x -1x = 7x + -7x Combine like terms: 7x + -7x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| -4(2p+4)-40=2(4p+4) | | -33+5y+3=2(4y-2)-2 | | 5(c-3)=6(c-5) | | x+.0875x=10 | | -5x-1=12 | | 2n-21=-28+3n | | 3x+16xy+16y= | | 5p-5=-41+p | | 8(4k-4)=-54k-32 | | 5x^2-2=9x | | -9=19(h-3) | | 4=0.2(r-0.08) | | x+.0875x=9 | | 5x+3-2x=-15 | | 6(x-4x)= | | 6z+4=z-2 | | 2n-1-3n=5n-7-3n | | 0.2t+.833=.666-t | | -.555x+.333=.222 | | 5.5x-4.5=6.5 | | -2(t-2)+4t=9t-9 | | -(7y+4)-(2y-5)=14-(5y-3) | | 8.6x+80.26=-11.4x+78.62 | | 8.6+80.26=-11.4+78.62 | | 10y-1-4y+8= | | 10-2b-3b=20 | | 3(x-2)-(x+6)=4(x-1) | | (2(x^2)+2)= | | (4y)(4y)= | | (M^0)(-4)= | | 3+2(x-7)=x-18 | | 24a^4-4a^4= |